Hypolipidemic Effects of Fermented Seaweed Extracts by Saccharomyces cerevisiae and Lactiplantibacillus plantarum - Yue, Qiulin; Wang, Zhongjian; Tang, Xueyang; Zhao, Chen; Li, Kunlun; Su, Le; Zhang, Song; Sun, Xin; Liu, Xinli; Zhao, Lin (Frontiers in Microbiology, 2021)
The fermentation of food materials with suitable probiotic strains is an effective way to improve biological activities. In this study, seaweed extracts were fermented by Saccharomyces cerevisiae and Lactiplantibacillus plantarum, and the hypolipidemic effects of the fermentation products were investigated. In vitro experiments suggested that fermented seaweed extracts have a high capacity for bile acid-binding. Additionally, a significant inhibitory effect against pancreatic lipase was observed. Furthermore, effects in hyperlipidemic mice were determined. Fermented seaweed extracts can alleviate lipid metabolism disorder. The administration of fermented seaweed extracts to mice showed decreased total cholesterol (TC), triglyceride (TG) and low-density lipoprotein cholesterol (LDL-C) levels and increased high-density lipoprotein cholesterol (HDL-C) levels. Combined, these results suggest that fermented seaweed extracts perform a potent hypolipidemic action, thus providing an effective method for the preparation of functional foods to combat cardiovascular diseases.